IMPLEMENTATION OF TERMINATION AND APPOINTMENT OF LAMPOKO VILLAGE EQUIPMENT, BALUSU DISTRICT, BARRU REGENCY - A. Pananrangi M (Sean Institute, 2022)
This study aims to provide an overview in understanding the implementation of the dismissal and appointment of the Lampoko Village, Balusu District, Barru Regency. The type of research used is a qualitative research type. Data collection techniques were carried out through observation, interviews and documentation. Then technical data analysis was carried out through data reduction steps, data presentation and conclusion drawing. The results showed that the process of dismissing and appointing village officials, Balusu District, Barru Regency was in accordance with the provisions of the Minister of Home Affairs Regulation Number 67 of 2017 concerning the Appointment and Dismissal of Village Apparatus.